Pemberdayaan Masyarakat Kecamatan Pesanggrahan di Bidang Ekonomi dan Lingkungan dalam Menghadapi Krisis Covid-19 - Bustami Bustami; Farell Pramuja; Aldo Reshwara; Hirda Umayyah; Ravellino Fahlepi; Iffani Nabila Zain; Muhammad Zaki Dama; Nur Shasqia Malewa; Shabrina Itsnaini Oktafira; Sita Permata Sari (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Student Community Service is activity by students with a cross-scientific and sectoral approach at certain times and placed in Indonesia. Pesanggrahan District is one of location choosen by IPB University which located in administrative area of South Jakarta. The purpose of this activity is business mentoring for MSMEs and the establishment of waste bank so that people are accustomed to living healthy. The activity was carried out from July to August 2020. The MSME mentoring program has succeeded in assisting 25 MSMEs in Pesanggrahan area by providing education about bookkeeping, making logos, improving product photos, and creating e-commerce accounts. In addition, a webinar on business strategy was also held which was attended by 39 participants. The community education program regarding waste has been carried out with the establishment of three waste banks in the Pesanggrahan area. Keywords: education, waste, MSME